Introduction of the leak-before-break (LBB) concept for cast iron water pipes on the basis of laboratory experiments. Issue 8 (14th September 2017) - Rathnayaka, Suranji; Shannon, Benjamin; Zhang, Chunshun; Kodikara, Jayantha
Abstract: Failure of cast iron water mains in Australia is a common occurrence. Water utilities are seeking solutions to optimise the renewal and rehabilitation of ageing cast iron critical water mains (diameter ≥ 300 mm). Failure pressures of three large-diameter cast iron pipe specimens (600 mm in diameter) were tested. A large corrosion patch was machined onto each pipe section to initiate pipe failure. A large corrosion patch and significant reduction (>90%) of pipe wall thickness were needed to fail the tested pipe specimens. All three pipes under test exhibited leaking before bursting, indicating that the concept of leak-before-break (LBB) could be used for pipe failure prevention. In addition, LBB provides valuable information that could be added to the pipe asset database to make better management decisions on repair or replacement along with all other asset information. The study also found that small corrosion patches (<50 mm) with low remaining wall thickness may cause pipe leaks, but are less likely to cause major pipe bursts.